Analisis Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage dan Kepemilikan Saham Publik Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Tahun 2017-2019) - Riska, Riska; Luhgiatno, Luhgiatno; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of profitability, firm size, leverage and public share ownership on the disclosure of social responsibility. The sample in this study amounted to 165 Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2017-2019 which were selected using purposive sampling. Methods of data collection is done through the method of documentation. This study uses multiple regression analysis. The results of this study indicate that profitability, leverage and public share ownership have no effect on CSR disclosure, while company size has a negative effect on CSR disclosure.Keywords: Profitability, Leverage, Company Size, Public Share Ownership, and CSR